Performance of OCDMA system using and subtraction technique based on EDW code - Shaban, Ihsan; Hasoon, Feras N.; Syed Alwee Aljunid, Syed Junid; Sahbudin, Shaari (Fachverlag Schiele & Schoen GmbH, 2009)
Link to publisher's homepage at http://joc-online.schiele-schoen.de